Consequences of Alloxan-Induced Diabetes on certain Hematological and Hepatic parameters in Albino Mice - Mahmoud Elderbi; Asma Omar; Hajer Omar; Ashref Elburi; MuatasemBellah Ibrahim (Khalij-Libya Journal of Dental and Medical Research, 2025)
Alloxan is widely used to induce diabetes in animal models because it selectively destroys pancreatic beta islets, which correlate with inverse change in the plasma concentration of insulin, resulting in beta cells necrosis. Diabetes mellitus is a metabolic disorder which affects humans of all ages and has become epidemic in the last few years. Oxidative stress in DM can contribute to various abnormalities in the physiology of blood cells and liver impairment. The primary goal of this study is to investigate how diabetes affects blood parameters and liver function in an animal model, which contributes to managing various complications in diabetic patients. Twenty male Swiss albino mice were housed at research lab in pharmacology department, faculty of medicine, Benghazi. Mice were fasted for 48 hours and then classified into two groups; the first group did not receive any treatment while the second group received a single intraperitoneal injection of freshly prepared alloxan 200mg/kg dissolved in normal saline (PH 4.5) with a concentration of 1%. After one month, the blood samples were collected from all mice and analyzed. The main outcome is that induction of diabetes in albino mice result in elevated blood glucose level, weight loss, low RBC and WBC counts, elevated platelets count, and liver impairment. The findings of this study align with previous research investigating that diabetes can result in anemia, immune suppression, and liver damage. However, translational explanations must account for species-specific responses and model limitations. يستخدم الألوكسان على نطاق واسع للحث على مرض السكري في النماذج الحيوانية لأنه يدمر بشكل انتقائي جزر بيتا البنكرياسية، التي ترتبط بالتغير العكسي في تركيز الأنسولين في البلازما، مما يؤدي إلى نخر خلايا بيتا. داء السكري هو اضطراب أيضي يصيب البشر من جميع الأعمار، وقد أصبح وباءً في السنوات القليلة الماضية. يمكن أن يساهم الإجهاد التأكسدي في حدوث تشوهات مختلفة في فسيولوجيا خلايا الدم وضعف الكبد. الهدف الأساسي من هذه الدراسة هو دراسة كيفية تأثير مرض السكري على بارامترات الدم ووظائف الكبد في نموذج حيواني، مما يساهم في إدارة المضاعفات المختلفة لدى مرضى السكري. تم إيواء عشرين فأرا سويسريا ذكرا في مختبر الأبحاث بقسم الصيدلة بكلية الطب بنغازي. تم صيام الفئران لمدة 48 ساعة ثم تم تصنيفها إلى مجموعتين؛ لم تتلق المجموعة الأولى أي علاج بينما تلقت المجموعة الثانية حقنة واحدة داخل الصفاق من الألوكسان الطازج 200 ملغم / كغم مذاب في محلول ملحي عادي وبعد شهر واحد، تم جمع عينات الدم من جميع الفئران وتحليلها. والنتيجة الرئيسية هي أن تحفيز مرض السكري في الفئران البيضاء يؤدي إلى ارتفاع مستوى السكر في الدم، وفقدان الوزن، وانخفاض عدد كرات الدم الحمراء وخلايا الدم البيضاء، وارتفاع عدد الصفائح الدموية، وضعف الكبد. تتوافق نتائج هذه الدراسة مع الأبحاث السابقة التي بحثت في أن مرض السكري يمكن أن يؤدي إلى فقر الدم وتثبيط المناعة وتلف الكبد. ومع ذلك، يجب أن تأخذ التفسيرات الترجمية في الاعتبار الاستجابات الخاصة بالأنواع والقيود النموذجية